2020
DOI: 10.1111/1759-7714.13446
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic yield of additional conventional transbronchial lung biopsy following radial endobronchial ultrasound lung biopsy for peripheral pulmonary lesions

Abstract: Background: Radial endobronchial ultrasound (R-EBUS) transbronchial lung biopsy (TBLB) improves the diagnostic yield from peripheral pulmonary lesions (PPLs). However, the small specimens obtained using small forceps through a guide sheath (GS) may impede diagnosis and molecular analysis. Here, we investigated the diagnostic significance of additional conventional TBLB with standard forceps after R-EBUS-GS-guided TBLB. Methods: We retrospectively reviewed data from 55 patients who underwent conventional TBLB a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 32 publications
0
26
0
1
Order By: Relevance
“…The complications of the procedures were comparable to those reported in previous studies conducted mainly in patients with bronchus sign positive PPLs. 7 11 12 To the best of our knowledge, this is the first study focusing on the utility of RP-EBUS-TBLB in bronchus sign negative PPLs.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The complications of the procedures were comparable to those reported in previous studies conducted mainly in patients with bronchus sign positive PPLs. 7 11 12 To the best of our knowledge, this is the first study focusing on the utility of RP-EBUS-TBLB in bronchus sign negative PPLs.…”
Section: Discussionmentioning
confidence: 96%
“…An EBUS image with the probe within the lesion was very closely related to the success of the diagnosis (OR, 28.50) in the bronchus sign negative PPLs, which agrees with most previous studies, including those on bronchus sign positive PPLs. 6 7 12 15 16 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We normally use a 1.95‐mm thin GS to introduce instruments when performing repeated conventional biopsies for the diagnosis of PPLs 33 . In the present study, however, a UTB was utilized as a thick GS, with “guided eyes” on the tip of the bronchoscope.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is important to develop strategies to determine if a small nodule is malignant when first identified. However, the traditional imaging test, such as CT and R-EBUS, cannot provide sufficient information to detect malignant lesions accurately [42][43][44]. For example, the CT images of 5 cases of patients in this study showed ground glass nodules (GGO).…”
Section: Discussionmentioning
confidence: 76%